Lingual Orthodontic Retreatment of an Adult Patient with Protruded Lips and a Missing Lower Incisor: A Case Report - Nguyen, Viet Anh; Pham, Thi Hanh; Nguyen, Thuy Anh (European Journal of General Dentistry, 2024)
Orthodontic retreatment in adult patients presents unique challenges and considerations. Previous dental intervention or even missing teeth may influence treatment planning and pose challenges for bracket bonding.A 23-year-old female patient sought orthodontic retreatment to address her chief complaint of upper lip protrusion. She had previously completed fixed labial orthodontic treatment involving the extraction of a lower central incisor.The diagnosis was a skeletal maxillary protrusion and mandibular dentoalveolar protrusion on dental class I and skeletal class II relationships.A nonsurgical camouflage treatment option was chosen, which involved the removal of the upper first premolars and lower right first premolar. The lower left canine, lateral, and central incisor were substituted with the lower left first premolar, canine, and lateral incisor, respectively. Lingual self-ligating brackets, straight archwires, and temporary anchorage devices were utilized. The treatment was completed after 32 months with an improved facial profile and a stable occlusion.This case report demonstrates the successful retreatment of an adult patient with lip protrusion and relapse of lower arch crowding using straight-wire lingual appliances and premolar extractions. This approach achieved optimal aesthetics and a stable occlusion, highlighting the effectiveness of lingual appliances in complex adult retreatment cases.
Keywords: case report; lingual brackets; tooth agenesis; lingual straight archwire; protrusion